Productivity, Efficiency and Logistics Performance Assessment of Humanitarian Relief Organizations - İbrahim Akben; Orhan Taşdoğan (Journal of Transportation and Logistics)
One of the most important stages of aid activities carried out by humanitarian aid organizations is logistics activities. These activities are generally carried out in various humanitarian areas such as food, health services, clothing, education, and psychological support. Therefore, their logistics performance is of great importance when humanitarian organizations deliver aid to a region where humanitarian crises occur. The main aim of this study is to evaluate the logistical performance of non-governmental organizations operating in the field of humanitarian aid to examine the variables that affect the logistic performance of organizations and to determine the effects of these variables. Due to the scope of work of domestic and foreign origin, non-governmental organizations operating in Turkey have been the main focus of research. A field study was conducted on these organizations, the data and information obtained were analyzed in the statistical analysis program, and the hypothesis of the research was tested. At the end of study, it was seen that productivity performance has a meaningful and positive effect on logistic performance. It has been determined that efficiency performance has significant but negative effect on logistic performance.